FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING SAHAM STUDI EMPIRIS PADA PERUSAHAAN PUBLIK DI INDONESIA - Amelia, Dewi; Citra, Prima (Jurnal Analisis Bisnis Ekonomi, 2007)
This study is purpose to examine and to verify empirically the influence of underwriter reputation, fiancial leverage, return on asset, earning per share, price earning ratio to underpricing. The analysis is based on the 41 initial public offerings firms during the period of 2002-2006. Regression analysis is used in testing the data in this study. Using a sample of Jakarta Stock Exchange, we provide evidence of statistically significant influence of financial leverage and price earnig ratio to underpricing. The fundings also indicate that the factors accounted for 43,50 pecent of the variance associated with underpricing.